THE RECEPTION OF DAJAL STORY IN THE SAIFU AD-DHARIB - Faiz Karim Fatkhullah; Tajudin Nur; Undang Ahmad Darsa (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2018)
This study reveals the story of Dajjal who experienced a shift in interpretation. This is due to the response of each reader with a different background. To disclose it, this research uses the reception theory proposed by Hans Robert Jauss. This research is the result of philology research from Saifu ad-Dharib (SaD) script. This manuscript was written by KH. Tubagus Ahmad Bakri, Purwakarta, West Java, with a thickness of 32 pages. Meanwhile, the section of the manuscript taken only the story of Dajjal contained in Chapter 4 and part of Chapter 5. From the results of the manuscript SaD taken only transliteration and translation. From the results of the study, it was found that the author of SaD responded that Dajjal in question is Ibn Sayyad. It is realized by the author that there are two opinions concerning the birth or previous Dajjal, but the author responds and interprets that Dajjal has been born ie that existed in the time of the Prophet Muhammad. In addition, Dajjal will come out with 70,000 followers who are mostly artists. The great Dajjal before the exit will be preceded by the existence of the small Dajjal-Dajjal which is now emerging, ie Persatuan Islam, Muhammadiyah, Wahabi, and Shi'a. This manuscript was born at the time of the condition of Muslims who are still in conflict, so the reception of Dajjal refers to the organization of the period above. The manuscripts of his day can be used as propaganda material.Keywords: Dajjal, reception theory, saifu ad-dharib RESEPSI CERITA DAJJAL DALAM NASKAH SAIFU AD-DHARIBAbstrakPenelitian ini  mengungkap cerita Dajjal yang mengalami pergeseran tafsir. Hal itu disebabkan karena adanya tanggapan dari setiap pembaca yang berlatar belakang berbeda. Untuk mengungkap itu, maka penelitian ini menggunakan teori resepsi yang dikemukakan oleh Jauss. Penelitian ini merupakan hasil penelitian filologi dari naskah Saifu ad-Dharib. Naskah ini ditulis oleh KH. Tubagus Ahmad Bakri, Purwakarta, Jawa Barat, dengan ketebalan naskah 32 halaman. Sementara itu, bagian naskah yang diambil hanya cerita Dajjal yang terdapat pada Bab 4 dan sebagian Bab 5. Dari hasil naskah SaD yang diambil hanya transliterasi dan terjemahan. Dari hasil penelitian ditemukan bahwa penulis SaD menanggapi bahwa Dajjal yang dimaksud adalah Ibnu Sahayyad. Disadari oleh penulisnya bahwa ada dua pendapat terkait lahir atau belumnya Dajjal, namun penulis menanggapi dan menafsirkan bahwa Dajjal telah lahir yakni yang ada pada zaman Nabi Muhammad saw. Selain itu, Dajjal akan keluar dengan disertai 70.000 pengikut yang sebagian besar adalah seniman. Dajjal besar sebelum keluar akan didahului dengan adanya Dajjal-Dajjal kecil yang sekarang ini sudah muncul, yaitu Persatuan Islam, Muhammadiyah, Wahabi dan Syi’ah. Naskah ini lahir di saat kondisi umat Islam yang masih saling bersitegang, sehingga resepsi terhadap Dajjal merujuk pada organisasi masa di atas. Naskah pada zamannya dapat digunakan sebagai bahan propaganda.Kata kunci: Dajjal, teori resepsi, saifu ad-dharib